Security and trends in wireless identification and sensing platform tags : advancements in RFID - Peris Lopez, Pedro, 1978-; Hernandez-Castro, Julio C., 1972-; Li, Tieyan (Premier reference source, 2013)
"This book highlights new research regarding wireless identification and sensing platform (WISP) tags, security, and applications, serving as a reference on WISP technology and presenting recent advances in this field"--Provided by publisher